The Impact Of Health Education On Improving The Knowledge Of Women 45–55 Years Old Considering Menopause; Review Of Literature - Yani, Tri Ardayani (Sahabat Publikasi Kuu, 2025)
In women who have reached the aging stage, menopause is a physiological condition marked by a decline in estrogen levels. Estrogen deficiency frequently results in symptoms that significantly interfere with women's daily activities and even jeopardize their pleasure at home. In Indonesia, menopause is thought to occur between the ages of 40 and 55 on average. According to World Health Organization projections, the number of women going through menopause is expected to rise from 107 million in 2025 to 373 in 2030, and then to 1.2 billion in 2030. Health education is one way to try to raise awareness about menopause. Increasing the awareness of women between the ages of 45 and 55 about menopause can be accomplished more effectively and appropriately through health education. A literature review methodology was used in the writing of this paper. In the review literature search technique, the search phrases